Britain's Butterflies A Field Guide to the Butterflies of Great Britain and Ireland – Fully Revised and Updated Fourth Edition - Newland, David; Still, Robert; Swash, Andy (WILDGuides, 2020)
A new and improved edition of the popular photographic field guideBritain's Butterflies is a comprehensive and beautifully designed photographic field guide to the butterflies of Britain and Ireland. Containing hundreds of stunning colour photographs, this extensively revised and updated new edition provides the latest information on every species ever recorded. It covers in detail the identification of all 59 butterfly species that breed regularly, as well as four former breeders, 10 rare migrants and one species of unknown status. The easy-to-use format will enable butterfly watchers—beginners or experts—to identify any species they encounter. Produced in association with Butterfly Conservation, this edition features new introductory sections on the identification of more difficult groups; revised maps that show the latest distributions recorded by the UK Butterfly Monitoring Scheme; expanded sections on food plants and on recording and monitoring; a new section on climate change; and a revised species order reflecting the latest taxonomy.Stunning colour plates show typical views of each butterfly species, including the various forms and common aberrationsDetailed species profiles cover adult identification; behaviour; habitat requirements; population and conservation; egg, caterpillar and chrysalis; and status and distribution, including up-to-date mapsPhotographs of the egg, caterpillar and chrysalis for every breeding speciesSections on biology, where to look for and how to identify butterflies and other essential informationFeatures new to this edition include introductory sections on the identification of difficult groups; the latest species information and distribution maps; expanded sections on food plants and on recording and monitoring; a section on climate change; and a revised species order reflecting the latest taxonomy